FENOMENA SHOUSHIKA DI JEPANG : PERUBAHAN KONSEP ANAK - Arsi Widiandari (IZUMI, 2016)
The focus of this study is the shoushika  phenomenon or decrease in the number of births that occurred in Japan from the perspective economic household in raising children. The research data was collected from several sources of statistical data  published by the Japanese government, Family Income and Expenditure Survey, and National Institute of Population and Social Security Research. Recently the delay of childbearing of young married couple is said to reason  of fertility decline. The high cost of children is said to be one of the causes of this delay. This paper will focus on the persistent low birthrate in Japan and the change of utility of children in Japan’s family.  This paper show that there’s a transition from traditional family to modern family that influence change of children utility from good utility become comsumption utility. The transition to consumption utility related to Japanese family expenditure especially what family give to their children.